Effect of ageing method, ageing period, cooking method and sample thickness on beef textural characteristics - Panea, B.; Sañudo Astiz, C.; Olleta, J.L.; Civit, D. (Spanish Journal of Agricultural Research, 2008)
The effect of the ageing method (bone-in or boneless), ageing period (7 or 14 days), cooking method (grilling or water bath preparation) and sample thickness (1, 2 or 4 cm) on the meat texture characteristics of the longissimus thoracis muscle of six young, commercial bulls was measured using a texture analyser incorporating compression and Warner-Bratzler devices. The sarcomere length of the raw meat and cooking losses were also recorded. The ageing method and ageing period had more influence on the textural properties studied than either the cooking method or sample thickness. Cooking losses were, however, mainly influenced by the cooking method. Although the cooking method had no significant effect on meat toughness, the meat tended to be tougher when grilled than when prepared in a water bath. Meat tenderness mainly improved during the first week of storage.